Modernity and Nature: Where did Rousseau Seek to Return? - Daraškevičiūtė, Vaiva (Religija ir kultūra, 2015)
[full article and abstract in Lithuanian; abstract in English] This article focuses on the nostalgic approach to nature represented in the philosophy of Jean-Jacques Rousseau. The position of Rousseau is treated as a model that reveals a correlation between a critical attitude toward becoming modern and a nostalgic approach to nature. With an analysis based on the interpretations of Jacques Derrida, Bernard Stiegler, Tracy B. Strong and other authors, this paper emphasizes the contradictoriness of Rousseau intention. The article comes to the conclusion that Rousseau’s intention of the return to nature belongs to a metaphorical dimension rather than to a practical one, and this supposes a paradoxical course of nostalgia in itself – the return to nature should be understood not as a nostalgia for the past, but as a nostalgia for the future and for a new, alternative human model. Finally, the article discusses the Lithuanian feast of Rasos, which came from an archaic, agriculture-centered world but is still celebrated in our times. It demonstrates a common background for both the feast and for Rousseau’s vision of return, which are related not only by a nostalgic approach to nature but also by the concept of nature as a substitute (in the sense of fiction). As in Rousseau’s thought, so in the feast of Rasos nature manifests itself through lack and absence – by losing its ontological dimension, nature becomes not an essential necessity but rather represents an aesthetical experience in the form of tradition and symbols.